Composite pre-reduced pellet quality as affected by reductant reactivity - Gupta R.C.; Misra S.N. (My University, 2025)
The composite pre-reduced (CPR) pellets have been developed to utilise steel plant waste fines (eg. Iron ore, flue dust, mill scale, coke, coal, lime etc.) into value added product suitable for blast furnace feed as metallised burden. This requires good reduction (%R), appreciable metallisation (%Femet), sufficient handling strength and low cost for acceptance as blast furnace feed. These properties could be achieved by optimising the process parameters. In this paper, the effect of reductant reactivity has been observed by studying the reduction behaviour of ore-char mixed composite pellet due to powdered coke, coal and woodchar while keeping the molar ratio of Fe2O3: C as 1: 3 and identical heating schedule. It was observed that highly reactive form of carbon in woodchar rendered more reduction (∼ 46% R) compared to coke (22%R) and coal (39.5%R) but woodchar also seem to cause severe pellet cracking than coke or coal. The cracking is mainly due to whisker type of iron growth caused by rapid reduction rate.